THE SIGNIFICANCE OF LEGAL REGULATION IN ENSURING CYBER SECURITY IN THE CONDITIONS OF WAR: EXPERIENCE FOR UKRAINE - Vladyslav Horulko (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. In the vast majority of countries, there is a constant trend towards a significant increase in the number and expansion of the spectrum of cyber-attacks with the aim of violating the confidentiality, integrity and availability of state information resources, in particular those distributed on the Internet and objects of critical information infrastructure.